Buddhismus und Christentum: Ein Vergleich im Licht fraktaler Strukturen - Schmidt-Leukel, Perry (Evangelische Theologie, 2023)
Comparative studies often present Buddhism and Christianity as religions marked by contradictory or even antagonistic features. The paper argues that this view is largely based on a homogenizing and essentializing perspective which does not do justice to the actual diversity found within both traditions. It further argues that major typological differences between both traditions reappear within each one of them and might be better understood as complementary than contradictory, that is, differences between a world-renouncing and a worldaffirming spirituality, impersonal and personal conceptions of Ultimate Reality, concepts of the mediators as enlightened teacher or divine incarnation and concepts of the path of salvation as one of self-help or other-help. The paper thus illustrates the theory that religious diversity displays, to a large extent, "fractal" patterns: The typological differences that constitute religious diversity at the inter-religious level replicate at the level of intrareligious diversity and even at the level of intra-subjective religious diversity. By getting a better understanding of such fractal patterns we will not only arrive at a new understanding of the relation between Buddhism and Christianity but of religious diversity in general, an understanding with far-reaching theological implications.